PHOTONIC INTEGRATED CIRCUIT AND ITS CALIBRATION - AVDIEIONOK, IRYNA; BOROVYTSKY , VOLODYMYR (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The article proposes a new structure of a photonic integrated circuit for multiplying vector signals by a matrix. The architecture and principles of operation of modern photonic integrated circuits according to the given classification are briefly described. The proposed system consists of three layers, which includes a radiating, receiving and intermediate block with apertures. The connection of the photonic integrated circuit to the necessary electrical circuit for the investigation of the output signals of the photonic integrated circuit is described. With the help of the electrical circuit, we can monitor and control the input signals on each waveguide of the radiating unit, and track the change of the output signals that have passed through the system and fixed at the output of each waveguide. In the course of the study, we develop graphs of the levels of input and output signals of the system. With the help of which we represent the system errors and the change of signals, which makes it possible to calibrate the system. Calibration of the photonic integrated circuit is carried out by calibrating all electrical elements of the radiation and the receiving unit. In the emitting unit, it is necessary to select the same LEDs according to their characteristics, and with the help of variable resistors, which are connected to each pair of LEDs, calibrate the LED to the same brightness. We control the uniformity of brightness with the help of an IR camera. To calibrate the receiving unit, we fix the shadow noise and enter the reference coefficients for each receiver. After all the units were configured, the system was tested. A block with a specific aperture location was created, and the output signal was removed. Based on the results of the study, we proved that the system calibration is correct and that the system is operational.
Keywords: multiplication of vector by matrix; optical waveguide; PIC research; photonic devices; optoelectronics